Synthesis and Conformational Analysis of 3,5,7-Triaryl-1,3,5,7-oxatriazocanes - Kakanejadifard, Ali; Zabardasti, Abedin; Kakanejadifard, Hadis (Asian Journal of Chemistry, 2010)
By condensation of arylamines and formaldehyde in equimolar ratio, using formic acid as catalyst and acetonitrile as a solvent at room temperature, 3,5,7-triaryl-1,3,5,7-oxatriazocanes (2-5) were formed. The composition and structural formula of all compounds were confirmed by elemental analysis, IR, MS and NMR spectroscopy methods. Theoretical calculation were used for conformational analysis of 3,5,7-tri(4-chlorophenyl)- 1,3,5,7-oxatriazocane in the gas phase at HF/3-21+ g(d,p) level of computational study. Results show that stability of various structures are in the order: crown > saddle > boat chair family.